2015
DOI: 10.1088/0004-637x/813/2/88
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Spiral Shocks Excited by Planetary-Mass Companions

Abstract: Direct imaging observations have revealed spiral structures in protoplanetary disks. Previous studies have suggested that planet-induced spiral arms cannot explain some of these spiral patterns, due to the large pitch angle and high contrast of the spiral arms in observations. We have carried out three-dimensional (3D) hydrodynamical simulations to study spiral wakes/shocks excited by young planets. We find that, in contrast with linear theory, the pitch angle of spiral arms does depend on the planet mass, whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
255
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(282 citation statements)
references
References 42 publications
25
255
2
Order By: Relevance
“…These studies have revealed spiral arms in a growing number of disks (Figure 1), both prominent near-symmetric twoarm spirals (e.g., Grady et al 2013;Benisty et al 2015) and more flocculent multiarm spirals on smaller scales and at lower contrast (e.g., Fukagawa et al 2004;Hashimoto et al 2011). Spiral arms can be produced by either gravitational instability (e.g., Rice et al 2003;Lodato & Rice 2004;Stamatellos & Whitworth 2008;Kratter et al 2010;Kratter & Lodato 2016) or the presence of massive companions (gas giant to stellar masses; e.g., Kley & Nelson 2012;Zhu et al 2015;Muñoz & Lai 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed spiral arms in a growing number of disks (Figure 1), both prominent near-symmetric twoarm spirals (e.g., Grady et al 2013;Benisty et al 2015) and more flocculent multiarm spirals on smaller scales and at lower contrast (e.g., Fukagawa et al 2004;Hashimoto et al 2011). Spiral arms can be produced by either gravitational instability (e.g., Rice et al 2003;Lodato & Rice 2004;Stamatellos & Whitworth 2008;Kratter et al 2010;Kratter & Lodato 2016) or the presence of massive companions (gas giant to stellar masses; e.g., Kley & Nelson 2012;Zhu et al 2015;Muñoz & Lai 2016).…”
Section: Introductionmentioning
confidence: 99%
“…3D hydrodynamical simulations of Zhu et al (2015) and Dong et al (2015) have shown that a massive planet of a few Jupiter mass in the outer regions would produce a pair of inner spiral arms, whose brightness and large pitch angle are compatible with the near-IR observations. Recent simulations of Bae et al (2017) have also shown that, for a disk with low viscosity (i. e. α ∼ 10 −4 ), a massive planet can also produce a secondary gap in the inner regions of the planet orbit.…”
Section: Possible Scenariosmentioning
confidence: 81%
“…Protoplanet solutions inside the scattered light cavity seem unlikely because the spiral arm pitch angles would require unphysical disk temperatures. -The surface brightness contrast and symmetry of the spiral arms indicate that a single massive protoplanet might have excited both the primary and secondary spiral arm interior of its orbit Zhu et al 2015;Fung & Dong 2015), however no gap is detected in scattered light beyond the spiral arms up to 1. 0.…”
Section: Discussionmentioning
confidence: 99%
“…Interference of different azimuthal modes results in a one-armed spiral which can be approximated with linear perturbation theory when M p /M * (H(r)/r) 3 , where M p is the mass of the protoplanet, M * the stellar mass, H(r) the pressure scale height, and r the disk radius. Higher order perturbation terms become important when M p /M * ∼ (H(r)/r) 3 which can lead to the presence of secondary spiral arm (Juhász et al 2015;Zhu et al 2015).…”
Section: Spiral Arms As Tracers Of Protoplanetsmentioning
confidence: 99%
See 1 more Smart Citation